Large Atrial Septal Defect Closure in a Patient with Severe Pulmonary Arterial Hypertension - Supomo Supomo (Korean Journal of Thoracic and Cardiovascular Surgery, 2017)
Patients with an atrial septal defect (ASD) and severe pulmonary arterial hypertension (PAH) are considered ineligible for defect closure surgery because of the risk of right ventricular decompensation and death after the operation. We report the case of a patient with large ASD and severe PAH who was able to undergo defect closure surgery successfully following long-term use of combined oral sildenafil and beraprost.